2018
DOI: 10.3390/nu10030349
|View full text |Cite|
|
Sign up to set email alerts
|

l-Carnitine Supplementation in Recovery after Exercise

Abstract: Given its pivotal role in fatty acid oxidation and energy metabolism, l-carnitine has been investigated as ergogenic aid for enhancing exercise capacity in the healthy athletic population. Early research indicates its beneficial effects on acute physical performance, such as increased maximum oxygen consumption and higher power output. Later studies point to the positive impact of dietary supplementation with l-carnitine on the recovery process after exercise. It is demonstrated that l-carnitine alleviates mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 92 publications
(120 reference statements)
0
81
0
1
Order By: Relevance
“…Furthermore, since it has been suggested that carnitine saves muscle glycogen and promotes fat oxidation [69], its integration is recommended to lose weight. Carnitine supplementation has been also reported to spare the use of amino acids as energy sources during exercise making them potentially available for new protein synthesis [70]. This notion justifies the use of carnitine to increase muscle mass during endurance exercise.…”
Section: Can Carnitine Supplementation Be Useful In Physical Exercise?mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, since it has been suggested that carnitine saves muscle glycogen and promotes fat oxidation [69], its integration is recommended to lose weight. Carnitine supplementation has been also reported to spare the use of amino acids as energy sources during exercise making them potentially available for new protein synthesis [70]. This notion justifies the use of carnitine to increase muscle mass during endurance exercise.…”
Section: Can Carnitine Supplementation Be Useful In Physical Exercise?mentioning
confidence: 99%
“…To this respect, it has been reported that muscle, with respect to other tissues, has a much lower net turnover of carnitine [96]; this feature makes muscle, unlike other tissues, particularly refractory to carnitine supplementation. Furthermore, we must consider that, in physiological conditions, carnitine is transported in the muscle against a concentration gradient and that OCTN2 transporter, having a Km value (3-5 µM) below plasma carnitine concentrations (30-50 µM), is saturated at the physiological carnitine concentrations [11,70]. Thus, it is unlikely that an increased plasma concentration of carnitine can cause higher transport of carnitine in the muscle.…”
Section: Can Carnitine Supplementation Be Useful In Physical Exercise?mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, recent studies have shown that anaerobic gut microbiota species can also generate TMAO via its atherogenic intermediate, dC0 due to chronic C0 exposure from the diet [68]. Nevertheless, C0 is still widely promoted as a nutritional supplement and ergogenic aide to improve fatty acid energy metabolism, as well as alleviate muscle injury from strenuous exercise [69]. Lastly, a series of plasma total (hydrolyzed) fatty acids had metabolic trajectories that increased when following a Western diet, which were directly associated with greater intake of total, saturated and trans fats, but lower consumption of poly:sat, vitamins and fruits & vegetables ( Table 2); these included a low abundance circulating trans fatty acid, C18:2n-6trans, as well as saturated fats (C14:0, C15:0), and omega-6 fatty acids, namely C18:3n-6cis and C18:2n-6cis.…”
Section: Novel Biomarkers Identified Following a Western Dietmentioning
confidence: 99%